Advances in Agile Methodologies for Project Management to Boost Efficiency in Energy Sector Operations - Oluwakemi Famoti; Rahman Akorede Shittu; Bamidele Michael Omowole; Godwin Nzeako; Ogechukwu Nwanneka Ezechi; Chikezie Paul-Mikki Ewim; Hope Ehiaghe Omokhoa (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
The application of Agile methodologies in the energy sector has gained attention as a promising approach to address the persistent challenges of project management, including complexity, cost overruns, and delays. Originally developed for the software industry, Agile practices emphasize flexibility, iterative development, and enhanced collaboration among diverse teams. This paper explores the potential of Agile methodologies to improve project management in energy sector operations, focusing on the benefits, challenges, and frameworks necessary for successful implementation. Through a comprehensive review of the literature and case studies from industries such as construction and manufacturing, the paper highlights the adaptability of Agile practices to energy projects, particularly in areas such as renewable energy, grid modernization, and smart infrastructure. The research identifies key considerations for adopting Agile, such as aligning Scrum, Kanban, or Lean principles with the unique characteristics of energy projects, including their large scale, long timelines, and regulatory complexities. The paper also examines the role of digital tools and emerging technologies, such as artificial intelligence, IoT, and big data, in supporting Agile workflows in energy projects. Furthermore, the study offers practical recommendations for energy organizations, including phased implementation strategies, training, and investment in collaborative tools. The paper concludes by emphasizing the long-term benefits of Agile for improving cost efficiency, project delivery timelines, and stakeholder satisfaction in the energy sector.